Afrisc Meowle: Exploring Race in the Old English Exodus. Issue 3 (May 2022) - Dockray-Miller, Mary
Abstract: An Afrisc meowle ("African woman") appears at the end of the Old English Exodus, a poem ostensibly celebrating religious freedom, migration, and divine justice. Amid the Hebrews' final celebration, the explicit inclusion of the Afrisc meowle 's racial difference from the Israelites exposes the horror and violence of the aftermath of war; a focus on her also invites questions about the poem's early medieval audience and how that audience could have understood her, especially since she does not appear in the source text of the Hebrew Bible. The scant critical analysis of this remarkable figure tends to provide a brief exegetical explanation before moving into more secure critical territory. My analysis of the Afrisc meowle reveals the limitations of source study and exegetical criticism for Exodus and for the field of medieval studies; she thus serves as a case study for this deeper theoretical problem in the field.